Corporate social responsibility and employee behavior: Evidence from mediation and moderation analysis. (27th February 2020) - Lu, Jintao; Ren, Licheng; Zhang, Chong; Wang, Chunyan; Ahmed, Rizwan R.; Streimikis, Justas
Abstract: Corporate social responsibility (CSR) has become a prominent subject due to its major implication for the practitioners in the corporate arena. Based on the theory of engagement, theory of social exchange, and theory of social identity, a conceptual framework was established in this study to evaluate the employee engagement (EE), and organizational commitment (OC) as a resultant of CSR initiatives. The study further examined the impact of distributive justice (DJ), procedural justice (PJ), and job satisfaction (JS) as mediating variables, and the influence of collectivism (COL) as a moderating variable between CSR initiatives and OC and EE. Data from 989 employees of the Pakistani pharmaceutical industry was collected and analyzed using the structural equation modeling and exploratory and confirmatory inferential models. Results demonstrate that CSR initiatives have a significant positive impact on OC and EE. Similarly, the mediation of JS, PJ, and DJ was established between the exogenous and the endogenous variables. Finally, the COL has a significant impact as a moderating variable between CSR initiatives, and OC and EE. The conclusions obtained in this study provide significantly practical and theoretical implications for managers of involved firms to improve employee behavior, mold employee attitude, and enhance organizational performance via CSR strategy, especially for firms located in countries along the route of belt and road initiative.